Monetary Policy Transmission and Economic Growth in Indonesia: An Error Correction Model Analysis, 2000-2023 - Farhan Firdaus; Nicholas Agustinus Napitupulu; Muhammad Farhan; Wildan Maulana Assani Mualim; Arina Romarina (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Indonesia’s economic performance over the past two decades has been shaped by persistent monetary fluctuations, particularly in inflation, policy interest rates, and the Rupiah exchange rate. These dynamics have contributed to recurring volatility in output and created challenges for maintaining stable and inclusive growth. This study aims to examine both the short-run and long-run effects of key monetary variables inflation, the BI policy rate, and the exchange rate on Indonesia’s economic growth during 2000-2023. Using annual macroeconomic data from BPS and Bank Indonesia, the analysis employs an Error Correction Model (ECM) to capture long-term equilibrium relationships and to identify adjustment patterns following short-term shocks. The results indicate a stable long-run cointegrating relationship among the variables. Inflation and the policy rate exert significant negative effects on economic growth, with their long-run impacts being stronger than their short-run influences. In contrast, Rupiah depreciation shows a modest but positive long-run association with growth, reflecting the role of external competitiveness. The error-correction term demonstrates a meaningful and gradual adjustment toward long-run equilibrium, suggesting that deviations from stability are corrected over time. Overall, the findings highlight the importance of maintaining credible price stability, calibrating interest-rate decisions carefully, and managing exchange-rate movements to support sustainable economic expansion. The study underscores that consistent and coordinated monetary policy remains essential for strengthening Indonesia’s long-term growth resilience.